Analysis of Flavanoids in Flour and Biscuit based on Chayote - Jamaludin M. Sakung; Sitti Rahmawati; Nursafitri Nursafitri; Husniah Muhtar (Jurnal Akademika Kimia, 2020)
Chayote-based flour and biscuits are the development of healthy food products that contain flavonoid compounds that can be used to protect and reduce skin damage to UV rays. This study aimed to determine the flavonoid content in chayote-based flour and biscuits using the AlCl3 method with a UV-Vis spectrophotometry at a wavelength of 520 and 700 nm. The results obtained the flavonoid levels in chayote-based flour and biscuits of 0.325±0.011 mg/L and 0.117±0.023 mg/L or equivalent to 0.812±0.028 mg/100 gram and 0.291±0.058 mg/100 gram. This study concluded that chayote-based flour and biscuits contained flavonoids can be used as a source of antioxidants and a source of beneficial nutrition.